Discovery and biological evaluation of nitrofuranyl-pyrazolopyrimidine hybrid conjugates as potent antimicrobial agents targeting Staphylococcus aureus and methicillin-resistant S. aureus - Saini, Sapna; Reddy, G. Lakshma; Gangwar, Anjali; Kour, Harpreet; Nadre, Gajanan G.; Pandian, Ramajayan; Pal, Sunny; Nandi, Utpal; Sharma, Rashmi; Sawant, Sanghapal D. (RSC Medicinal Chemistry, 2025)
Nitrofuran and pyrazolopyrimidine-based compounds possess a broad antimicrobial spectrum including Gram-positive and Gram-negative bacteria. In the present work, a series of conjugates of these scaffolds was synthesized and evaluated for antimicrobial activity against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA). Many compounds showed MIC values of <= 2 mu g ml-1, with compound 35 demonstrating excellent activity (MICs: 0.7 and 0.15 mu g ml-1 against S. aureus and MRSA, respectively) and safety up to 50 mu g ml-1 in HepG2 cells. Compound 35 also exhibited no hemolytic activity, biofilm eradication, and effectiveness against efflux-pump-overexpressing strains (NorA, TetK, MsrA) without resistance development. It showed synergistic effects with vancomycin (S. aureus) and rifampicin (MRSA). Mechanistic studies revealed that compound 35 exhibits good membrane-targeting abilities, as evidenced by DAPI/PI staining and scanning electron microscopy (SEM). In an intracellular model, it reduced bacterial load efficiently in both S. aureus and MRSA strains. With a strong in vitro profile, compound 35 demonstrated favorable oral pharmacokinetics at 30 mg kg-1 and potent in vivo anti-MRSA activity, highlighting its potential against antibiotic-resistant infections.

Interrupted borrowing hydrogen strategy enabled aminomethylation and direct cross-dehydrogenative coupling strategy enabled dicarbonylation reactions of imidazo[1,5-a]pyridines - Mahajan, Shivangani; Bag, Debojyoti; Kour, Harpreet; Sawant, Sanghapal D. (Chemical Communications, 2025)
Herein, we disclose the development of novel aminomethylation and dicarbonylation reactions of imidazo[1,5-a]pyridines. The developed aminomethylation strategy involves a Pd-catalyzed interrupted borrowing hydrogen strategy by utilizing MeOH as the methylene source. A wide variety of imidazo[1,5-a]pyridines and secondary amines were explored for the developed strategy. The established imidazo[1,5-a]pyridine dicarbonylation strategy involves a catalyst/additive-free direct cross-dehydrogenative coupling reaction between imidazo[1,5-a]pyridines and 2-oxoaldehydes.

Elucidating the potential of novel class biphenyl-phenyl acetate, IDD-AN-A1, an inhibitor targeting Isocitrate Lyase in Mycobacterium tuberculosis: a target to lead approach - Negi, Anjali; Perveen, Summaya; Kour, Harpreet; Sawant, Sanghapal D.; Sharma, Rashmi (Bioorganic Chemistry, 2026)
Isocitrate lyase (ICL), a pivotal enzyme of the glyoxylate shunt pathway in Mycobacterium tuberculosis (Mtb), represents an attractive target for the development of new anti-tuberculosis (TB) therapeutics. In this study, we identified 2-methoxy-4-((nitrosooxy)methyl)phenyl 2-(2-fluoro-[1,1 `-biphenyl]-4-yl)propanoate (IDDAN-A1) as a potent inhibitor of Mtb ICL. The compound exhibited strong activity against Mtb, with a minimum inhibitory concentration of 6.25 mu g/mL, and demonstrated potent inhibition in enzyme-based assays targeting ICL. Molecular docking studies further supported Mtb ICL as the potential molecular target of this compound. Cytotoxicity and hemolytic assays revealed a favorable safety profile for the compound with selectivity index >10. In combination studies, it exhibited additive and synergistic activity with the frontline drug Rifampicin and Delamanid respectively. Additionally, ex vivo assays simulating the intracellular environment of the pathogen demonstrated strong inhibitory potency. In vitro inhibition studies further confirmed the bacteriostatic nature of the compound across different concentrations. Collectively, these findings demonstrate that this molecule possesses promising anti-tuberculosis activity by targeting the ICL enzyme in Mtb.
Keywords: Anti-tuberculosis activity; Ex vivo; Isocitrate lyase; tuberculosis

Sulfonyl pyrazoles as sustainable dual functional group transfer reagents: AlCl3 promoted transfer of sulfonyl and pyrazole groups - Kour, Harpreet; Mahajan, Shivangani; Ahmed, Sumeer; Birajdar, Ram; Verma, Praveen Kumar; Singh, Parvinder Pal; Sawant, Sanghapal D. (Journal of Organic Chemistry, 2026)
Herein, we report sulfonyl pyrazoles as sustainable dual-functional group transfer reagents for the transfer of two different functional groups to two different acceptors under mild conditions facilitated by AlCl3. The transformation proceeds via two distinct transition states: in the first, AlCl3 activates the S-N bond toward cleavage, and in the second, a sulfoximine nucleophilically attacks the sulfonyl group, resulting in the elimination of the pyrazole moiety. This process yields sulfonyl amidines, compounds with significant medicinal relevance, while the liberated pyrazole effectively participates in subsequent reactions with Michael acceptors. Notably, the protocol operates without the need for transition-metal catalysts and exhibits broad substrate scope along with excellent functional group tolerance.